Aggregation‐Induced Anti‐Kasha Emission: Unraveling Multimodal Luminescence Mechanisms in a Single Molecule With Five Morphologies - Ling Yu; Yuzhang Liu; Dakai Zhou; Zhigang Ni; Shijun Li; Chuluo Yang (Aggregate)
ABSTRACT In recent years, the exploration of emission pathways from high‐excited states in organic luminogens has received extensive attention owing to the anti‐Kasha's rule emission with the potential of improving the exciton utilization. However, it is extremely difficult to predict the anti‐Kasha effect and estimate the luminescent mechanism of high‐energy excited states. We here present a rational design on the basis of the intermolecular noncovalent interactions to achieve the purpose of altering the molecular optoelectronic properties and regulating the distribution of high‐energy excited state. The emitter, p‐Py‐SO2‐DMAC, with π–π dimer stacking is designed and synthesized, which not only exceptionally shows five aggregation morphologies and presents the infrequent aggregation‐induced anti‐Kasha's rule emission, room‐temperature phosphorescence (RTP), and mechanoluminescence (ML) behaviors simultaneously, but also possesses the features of thermally activated delayed fluorescence (TADF) and aggregation‐induced emission (AIE). The multiple luminescent mechanisms have been scientifically verified by experimental and theoretical investigations.